The curriculum as a site of counter politics: theorising the 'domain of the sayable'. Issue 1 (2nd January 2018) - Teague, Laura
Abstract: Whilst there has been increasing focus on the impact of neoliberal education policy on the curriculum covered in schools, as well as on teacher and student subjectivities, less research has been done on the possibility, or otherwise, for teachers to challenge curriculum constraints. Arguing that these curriculum constraints are not simply imposed by an external censor, this article takes up Judith Butler's concept of the 'domain of the sayable' to theorise what it is possible to imagine teaching in the primary school classroom in the first place. I draw on two different ethnographic data episodes to explore the parameters of the domain of the sayable in the space of the classroom in which I taught, mapping the silences and sudden swerving away from topics that seem to be straying close to what is impossible to say or hear. This process offers new insight into how we might conceptualise teacher resistance and counter politics within the current educational policy milieu in the United Kingdom.